MARKETING SYSTEMS FOR LIVESTOCK AND POULTRY: THE CASE IN CEBU, PHILIPPINES - Mondejar, Hershey P (Journal of Agriculture and Technology Management, 2022)
In the Philippines, one of the weaknesses considered in the livestock industry is a poor livestock marketing system affecting the profit of marginal small- scale livestock farmers. This study aimed to assess and describe the marketing system of cattle, goat, swine, and chicken in the province of Cebu. It sought to identify the determinants of effective livestock and poultry marketing and their influence on prices of the livestock; map the marketing channel of these animals; and solicit suggestions from livestock and poultry farmers, middlemen, and buyers for the improvement of the livestock marketing system. Findings show that the marketing system for most livestock is characterized by the traditional system wherein traders buy the animals at the farmers’ place then they bring the animals to the auction market. These animals are then sold to another trader at the auction market on a cash basis using the eye appraisal system, known as” mata-mata “ system. Transaction is on a cash basis. However, when the farmer needs cash, he directly delivers and sells the animals to the auction market by himself. There are three different marketing channels for cattle, goat, and swine before they reach the consumers. The marketing channel for chickens is the simplest. The lowest auction prices for livestock is in the month of June and livestock are priced the highest during the month of December. Farmers recognized the importance of using a standard weighing scale which should be provided by the local/provincial government to attain fair trading for farmers, traders and buyers; farmers should have access to market information through the provision of digital electronic display board where prevailing market price is displayed, shortening the market channel flow, and constant presence of personnel from LGU were the suggestions from the respondents to have an efficient marketing system at the livestock auction market.